Socio-Economic and Demographic Correlates of Non-communicable Disease Risk Factors Among Adults in Saudi Arabia - Al-Hanawi, Mohammed Khaled; Keetile, Mpho (Frontiers in Medicine, 2021)
Background: Over the past two decades, Saudi Arabia has made significant improvements in its population's health standards. These improvements have been coupled with an increase in risk factors related to non-communicable diseases (NCD) and a dramatic shift in the burden of disease profile. This study aims to provide empirical evidence on the socio-economic and demographic correlates of NCD risk factors among adults in Saudi Arabia. Methods: The data used for this study is secondary data derived from the Saudi Health Interview Survey (SHIS) conducted in 2013. The SHIS used a cross-sectional survey design to derive a multistage representative sample of adults to estimate the prevalence of NCD risk factors. Risk factors considered for analyses in this study were; current tobacco use, low fruit and vegetable consumption, low physical activity, overweight/obesity and hypertension. The survey covered all regions in Saudi Arabia using probability proportional to size measures. A total of 10,735 adults aged 15 years and above completed the survey questionnaire. Logistic regression analysis was conducted to examine the socio-economic and demographic correlates of NCD risk factors among adults in Saudi Arabia. Results: The prevalence of NCD risk factors were as follows: current tobacco use, 12.1%; low fruit and vegetable consumption, 87%; low physical activity, 94.9%; overweight/obesity 65.1%; and hypertension, 37.5%. The multivariate analysis results indicate that significant correlates of overweight/obesity and hypertension were being female, a government employee, income level, and education levels. On the other hand, current tobacco use and low fruit and vegetable consumption were generally associated with age, self-employment and being a student. For lifestyle factors, overweight/obesity was high among individuals who reported low fruit and vegetable consumption, while hypertension was high among current tobacco users and overweight/obese adults. All comparisons were statistically significant at p < 0.05. Conclusions: This study's findings indicate a high prevalence of chronic NCD risk factors in Saudi Arabia's adult population. This study implied that there is a need for a reduction in life-damaging behaviors among the adults through the adoption of healthy lifestyles such as physical activity and nutritious diets. Moreover, a reduction in the prevalence of chronic NCD risk factors among different socio-economic groups in Saudi Arabia through healthy lifestyles will have far-reaching results.